(untitled) (REMUNOM, 2025)
The Brazil nut is a native species of Brazil, playing a fundamental role in the local economy and in the conservation of biodiversity. In the northern region, the Brazil nut deserves attention, as it is a source of income for numerous communities. However, its extraction faces challenges such as environmental and climate issues. Therefore, considering the importance of the Brazil nut and the direct influence of precipitation variability and changes in land use and land cover in agriculture, we sought to understand how these factors may be affecting the agricultural productivity of the Brazil nut in the municipality of Acará from 2016 to 2021. To characterize land use and land cover, data from Mapbiomas were used, while for the spatial and temporal analysis of precipitation in the municipality of Acará, a CHIRPS precipitation dataset was used. These data were extracted and processed in GrADS. To analyze the development of agricultural production in the study region, data from the Brazilian Institute of Geography and Statistics (IBGE) were obtained. During the period analyzed in the study, a reduction in the area of ​​forest formation was observed, indicating the environmental vulnerability of the region. Regarding annual precipitation, it is possible to observe that, in 2016, the distribution of precipitation varied between 2800 and 3000 mm, while in 2021, a large part of the precipitation distribution was between 3000 and 3400 mm. Agricultural production in the municipality of Acará, in Pará, stands out as the main economic activity in the region.